Association of circulating proprotein convertase subtilisin/kexin type 9 concentration with coagulation abnormalities in patients with primary membranous nephropathy - Huizi Zhu; Qian Meng; Xiang Liu; Chunjuan Zhai; Jing Sun; Rong Wang; Liang Xu; Xiaowei Yang (Renal Failure)
Objectives The aims of the study were to explore the potential associations between plasma proprotein convertase subtilisin/kexin type 9 (PCSK9) and coagulation indexes in patients with primary membranous nephropathy (PMN).Methods A total of 87 patients diagnosed with PMN were enrolled in our study. 30 healthy participants were recruited to match PMN participants. Plasma PCSK9 concentrations were tested by enzyme-linked immunosorbent assay (ELISA). Correlations between PCSK9 and coagulation abnormalities in patients with PMN were analyzed using univariate and multiple linear regression analysis.Results Plasma PCSK9 levels in patients with PMN were significantly higher than that in healthy controls [232.0 (143.5, 359.5) ng/mL vs. 166.8 (129.7, 199.7) ng/mL; p = 0.001]. Plasma levels of PCSK9 were positively correlated with factor VIII, factor IX, factor XI, log-transformed tissue factor, protein C and protein S (r = 0.267, p = 0.013; r = 0.496, p < 0.001; r = 0.217, p = 0.045; r = 0.584, p < 0.001; r = 0.372, p = 0.001; r = 0.282, p = 0.011). In multiple linear regression analysis, PCSK9 concentration was independently and positively correlated with factor VIII, factor IX, and tissue factor (β = 0.186, p = 0.047; β = 0.325, p = 0.001; β = 0.531, p < 0.001; respectively). PCSK9 concentration was independently and negatively correlated with PT (β= −0.343, p = 0.011).Conclusion Plasma PCSK9 levels had good positive correlations with procoagulant clotting factors and negative correlations with PT in PMN, which might provide novel information with regard to PCSK9 and hypercoagulability in PMN.